2020
DOI: 10.1029/2019gc008353
|View full text |Cite
|
Sign up to set email alerts
|

Across‐Arc Diversity in Rhyolites From an Intra‐oceanic Arc: Evidence From IODP Site U1437, Izu‐Bonin Rear Arc, and Surrounding Area

Abstract: Felsic magmas from the Izu‐Bonin rear arc have compositions that resemble average continental crust in some respects. In order to understand their origin, we studied 1.1–4.4 Ma tephras in a rear‐arc drill core from International Ocean Discovery Program Expedition 350, Site U1437. They provide a well‐dated record of changing magmatic compositions during the early stages of the most recent episode of Izu‐Bonin arc rifting. Based on our comprehensive recontextualization of published analyses of <7 Ma regional dre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 102 publications
(235 reference statements)
1
19
0
Order By: Relevance
“…The age and composition of tuff‐rich Lithologic Unit IV are similar to those of lava dredged from the Manji summit where mineralized plutonic rocks (tonalites) also are exposed (Ishizuka et al, ; Tamura et al, 2015). The age and composition of tuffs in Lithologic Unit II are somewhat similar to those of rhyolite pumice from Meireki, the next seamount east of Manji (Heywood et al, ; Hochstaedter et al, ; Ishizuka et al, ) and identified in Figure b.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…The age and composition of tuff‐rich Lithologic Unit IV are similar to those of lava dredged from the Manji summit where mineralized plutonic rocks (tonalites) also are exposed (Ishizuka et al, ; Tamura et al, 2015). The age and composition of tuffs in Lithologic Unit II are somewhat similar to those of rhyolite pumice from Meireki, the next seamount east of Manji (Heywood et al, ; Hochstaedter et al, ; Ishizuka et al, ) and identified in Figure b.…”
Section: Introductionsupporting
confidence: 56%
“…The chemical evolution of the Izu volcanic front is well known from studies of bulk discrete ash and tuff intervals (sometimes called turbidites), and their individual vitriclasts, in ODP cores from the forearc (Bryant et al, ; Gill et al, ; Straub et al, ). One rationale for IODP Expedition 350 was to do the same for the rear arc, and some studies of discrete ash and tuff intervals from all Lithologic Units except III are underway (Heywood et al, ; Miyazaki et al, ; Sato et al, ; Schindlbeck et al, ). The tuffaceous mud(stone)s are compromised for this purpose because they contain variable amounts of foreign silicate material, bioclasts, and volcanic material from the volcanic front.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Izu arc is a very suitable place in which to study oceanic arcs for many reasons: (1) the weak influence of crustal contamination relative to mature island arcs (Savov et al, 2006;Stern et al, 2003;Tollstrup et al, 2010); (2) many samples are available from across the arc including the forearc, active magmatic arc, rear-arc rifts and cross chains, and backarc basin (Shikoku Basin); (3) the composition of the subduction inputs (the mantle wedge, subducting sediment, and altered oceanic crust [AOC]) is well known (Chauvel et al, 2009;Hauff et al, 2003;Kelley et al, 2003;Plank et al, 2007); and (4) no slab material has been removed into an accretionary complex, resulting in complete subduction. Many geochemical studies have been conducted in this arc (e.g., Heywood et al, 2020, and references therein), and numerous sites have been drilled in the arc front and forearc regions by ODP Legs 125 and 126 and IODP Leg 352, but there had been no drilling in the rear-arc region prior to IODP Exp. 350 (Tamura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%